Qur'an-Based Learning Model in Improving Arabic Language Skills in Early Childhood - Dede Nursamsy (Al-Banat: Journal of Early Childhood Islamic Education, 2025)
This study aims to develop and evaluate the effectiveness of a Qur'an-based learning model in improving Arabic language skills in early childhood. This research uses a qualitative approach with a case study design involving two Islamic education-based PAUD institutions in Bandung city. Data w ere collected through interviews with institution managers, educators, and parents, as well as direct observation in the classroom. The results show that the Qur'an-based learning model is effective in improving children's understanding of Arabic vocabulary related to religious teachings, such as prayer and worship. The children showed high enthusiasm and quickly memorized the vocabulary taught, as they associated the Arabic language with the spiritual meanings in the Qur'an. Nonetheless, the study also identified challenges related to time constraints in the curriculum and difficulties in thoroughly integrating religious values in Arabic language learning. Therefore, it is recommended to develop a more balanced curriculum and more integrated teaching materials between language and religious values. Overall, the results of this study suggest that Qur'an-based Arabic language teaching can be an effective model in early childhood education, with a positive impact on children's language and character development.